Advances in ubiquitous computing: cyber-physical systems, smart cities and ecological monitoring Vol.9 - Neustein, Amy (London: Academic Press / Elsevier, 2020)
"Advances in Ubiquitous Computing: Cyber-Physical Systems, Smart Cities and Ecological Monitoring debuts some of the newest methods and approaches to multimodal user-interface design, safety compliance, formal code verification and deployment requirements, as they pertain to cyber-physical systems, smart homes and smart cities, and biodiversity monitoring. The contributors, who are distinguished members of universities and research centers in Europe, South Asia, Africa, and the US, have been hand selected by the editor of this volume because of their outstanding work in pervasive computing. In this anthology the authors assiduously examine a panoply of topics related to wireless sensor networks. Those topics include interacting with smart-home appliances and biomedical devices, and designing multilingual speech recognition systems that are robust to vehicular, mechanical, and other noises common to large metropolises. The authors also recognize that in building smart cities there is a pressing need for voice biometrics through which one can validate a person's identity over a wireless medium. In laying a foundation for the new methods and approaches to pervasive computing, this book gives the reader an understanding of the true challenges in designing smart cities, smart homes and smart communities, and in the architecture of a system for performing high-level ecological monitoring. This book is an invaluable reference to system designers and biomedical scientists, as well as emergency healthcare management agencies and first responders in the field"--
Keywords: Networks; Database; Ecological monitoring; Wireless sensor network